Research and Development of Uncertainty Relations, and Reconsider and Description of Duality - Chang, Yi-Fang (European Journal of Applied Sciences, 2021)
First, based on the uncertainty principle in quantum theory and new generalized uncertainty principle, we research uncertain relations of entropy, information and thermodynamics, and propose the speed of light and some fundamental constants should be uncertain. Next, in the quantum entangled states, velocities of different phases may be superluminal, and obey possibly general Lorentz transformation (GLT). Third, we search its possible development in superstring, and the extensive quantum theory, various matters and different phases, etc. Fourth, the duality exists probably only under interactions. Some nonlinear quantum equations and wave equations have soliton solutions, which correspond to particles. This is mathematical description of wave-particle duality. Fifth, based on the soliton-chaos double solutions of nonlinear equations, we propose the field-particle duality, and field (wave)-quantum-chaos ternary. Sixth, the irreversibility and statistics are discussed, and we derive operators of entropy, etc. New measuring technology and some developed theories already challenge the uncertainty principle and duality, which may not be held under certain conditions, and must be modified and developed.